2014
DOI: 10.1002/ejoc.201402706
|View full text |Cite
|
Sign up to set email alerts
|

Syntheses of 4‐Substituted 2‐(Trichloromethyl)quinazolines under Mild Conditions by Benzyne [4+2] Cycloaddition

Abstract: An experimentally simple and convenient synthesis of 4‐susbstituted 2‐(trichloromethyl)quinazolines by cycloaddition of benzyne with 2‐(trichloromethyl)‐1,3‐diazabutadienes was developed. The 2‐(trichloromethyl)‐1,3‐diazabutadienes (R1 = H and Me) were prepared from trichloroacetamidine and the appropriate N,N‐dimethylamide dimethyl acetal or from trichloroacetamidine and a Vilsmeier–Haack reagent containing an aryl group.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
13
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 36 publications
(49 reference statements)
0
13
0
Order By: Relevance
“…nately, most of these 1,3-diazadienes are substituted with an alkyl or aryl group at position N-1, and it is thus not possible to obtain aromatic compounds. [20][21][22][23][24] As part of an ongoing study on the cycloaddition reaction of 1,3-diazadienes, our group previously reported some strategies for the preparation of NH-2-trichloromethyl-1,3-diaza-1,3-butadienes and showed their utility for the construction of pyrimidine 25,26 and quinazoline 27 derivatives by cycloaddition reactions mainly with electron-deficient acetylenes or benzyne. Herein, we now describe the synthesis of trifluoroacetamidine 1 (Scheme 1) and its preliminary study as a suitable building block for the synthesis of 2-trifluoromethyl-1,3-diazabutadienes, and the use of the latter as intermediates, particularly in cycloaddition reactions for the construction of 2-trifluoromethylpyrimidines.…”
Section: Syn Thesismentioning
confidence: 99%
See 1 more Smart Citation
“…nately, most of these 1,3-diazadienes are substituted with an alkyl or aryl group at position N-1, and it is thus not possible to obtain aromatic compounds. [20][21][22][23][24] As part of an ongoing study on the cycloaddition reaction of 1,3-diazadienes, our group previously reported some strategies for the preparation of NH-2-trichloromethyl-1,3-diaza-1,3-butadienes and showed their utility for the construction of pyrimidine 25,26 and quinazoline 27 derivatives by cycloaddition reactions mainly with electron-deficient acetylenes or benzyne. Herein, we now describe the synthesis of trifluoroacetamidine 1 (Scheme 1) and its preliminary study as a suitable building block for the synthesis of 2-trifluoromethyl-1,3-diazabutadienes, and the use of the latter as intermediates, particularly in cycloaddition reactions for the construction of 2-trifluoromethylpyrimidines.…”
Section: Syn Thesismentioning
confidence: 99%
“…In previous reports we have described that trichloroacetamidine can be condensed either with amide acetals 25 or with chloromethaniminium salts, also known as Vilsmeier-Haack reagents. 26,27 It was thought that trifluoroacetamidine 1 might react with these electrophilic agents in an analogous manner. This supposition proved to be correct when 1 was treated with a slight excess of N,N-dimethylformamide dimethylacetal (1.2 equiv) in tetrahydrofuran solution at room temperature for 16 hours, which led to the formation of 2-trifluoromethyl-1,3-diazabutadiene 2a in 95% yield in crude form (Scheme 2).…”
Section: Scheme 1 Synthesis Of Trifluoroacetamidinementioning
confidence: 99%
“…Our initial studies were based on the erroneous assumption that these 2-(trichloromethyl)-1,3-dienes 4 would be unstable in the free form, and that purification by column chromatography over silica gel might not be possible because of the tendency of 4 to undergo fragmentation reactions. 26 Therefore the liberation from its salt form 3 with a base was undertaken on the expectation that 4-phenyl-2-(trichloromethyl)-1,3-diaza-1,3-butadiene 4a would be obtained in crude form. Fortunately, when this crude 1,3-diazadiene was purified by column chromatography, 4a was obtained as a stable solid, and the best conditions for its generation were investigated ( Table 1).…”
Section: Scheme 2 Synthesis Of 4-phenyl-2-(trichloromethyl)-13-diazamentioning
confidence: 99%
“…9,12 A variety of 1,3-diazadienes as 4π components in cycloaddition reactions have been reported, such as [4+1] cycloaddition process with isocyanides, 13 the Simmons-Smith reagent; 14 [4+2] with acetylenic esters, 15,16 enamines, 17 oxazolinones, 18 sulfenes, 19 nitriles, 20 and recently with benzyne intermediates. 21 Particular interest has been given to the cycloaddition reactions of 1,3-diazabutadienes with ketenes; they are reported to undergo [4+2] [22][23][24][25] as well [2+2] [26][27][28][29][30] cycloaddition reactions leading to several different pyrimidinones and azetidinones. Ketenes are highly electrophilic intermediates, readily generated in solution by reaction of acyl chlorides with non-nucleophilic bases, such as a tertiary amine.…”
mentioning
confidence: 99%
“…We have previously demonstrated the synthetic utility of 1,3-diazabutadienes bearing a hydrogen on N-1 in cycloaddition reactions for the preparation of various aromatic heterocyclic compounds. 16,21,34,35 In connection with our studies directed at the development of new synthetic methods to prepare 2-(trichloromethyl)pyrimidine derivatives and their potential application in medicinal chemistry, we have been interested in studying the reactivity of these 1-unsubstituted 2-(trichloromethyl)-1,3-diazabutadienes, since these kinds of compounds can undergo cycloaddition reactions with ketenes to produce 2-(trichloromethyl)pyrimidin-4-ones, potential valuable intermediates to build 2-(trichlorometh-…”
mentioning
confidence: 99%